Functional analysis of a Wheat Homeodomain protein, TaR1, reveals that host chromatin remodelling influences the dynamics of the switch to necrotrophic growth in the phytopathogenic fungus Zymoseptoria tritici. Issue 2 (30th January 2015) - Lee, Jack; Orosa, Beatriz; Millyard, Linda; Edwards, Martin; Kanyuka, Kostya; Gatehouse, Angharad; Rudd, Jason; Hammond‐Kosack, Kim; Pain, Naomi; Sadanandom, Ari
Summary: A distinguishing feature of Septoria leaf blotch disease in wheat is the long symptomless growth of the fungus amongst host cells followed by a rapid transition to necrotrophic growth resulting in disease lesions. Global reprogramming of host transcription marks this switch to necrotrophic growth. However no information exists on the components that bring about host transcriptional reprogramming. Gene‐silencing, confocal‐imaging and protein–protein interaction assays where employed to identify a plant homeodomain (PHD) protein, TaR1 in wheat that plays a critical role during the transition from symptomless to necrotrophic growth of Septoria. TaR1‐silenced wheat show earlier symptom development upon Septoria infection but reduced fungal sporulation indicating that TaR1 is key for prolonging the symptomless phase and facilitating Septoria asexual reproduction. TaR1 is localized to the nucleus and binds to wheat Histone 3. Trimethylation of Histone 3 at lysine 4 (H3K4) and lysine 36 (H3K36) are found on open chromatin with actively transcribed genes, whereas methylation of H3K27 and H3K9 are associated with repressed loci. TaR1 specifically recognizes dimethylated and trimethylated H3K4 peptides suggesting that it regulates transcriptional activation at open chromatin. We conclude that TaR1 is an important component for the pathogen life cycle in wheat that promotes successful colonization by Septoria.